The Effectiveness of Law Enforcement Against Traffic Violations in Efforts to Mitigate Traffic Accidents (A Research Study at the Labuhanbatu Police Resort) - Welli Nirpa Pasaribu; Siregar, Mhd. Azhali; Suci Ramadhani (CERED Indonesia Institute, 2025)
According to the Law of the Republic of Indonesia Number 22 of 2009 concerning Traffic and Road Transport, traffic police are not only responsible for law enforcement but also for road and traffic safety, including the collection, monitoring, processing, and presentation of traffic data. Therefore, a reliable and efficient source of traffic accident data is crucial for traffic police. The problem formulation includes the factors that cause traffic accidents, prevention efforts and handling of traffic violations in the jurisdiction of the Labuhanbatu Police Resort, and the effectiveness of law enforcement against traffic violations to reduce the number of traffic accidents in the jurisdiction of the Labuhanbatu Police Resort. This research method is descriptive analytical, a type of empirical legal research, data collection methods using field studies and library studies, data analysis techniques with qualitative descriptive, and the data sources from primary legal materials, secondary legal materials, and tertiary legal materials, as well as analysis techniques. The factors causing traffic accidents include legal factors, road factors, driver factors, pedestrian factors, and vehicle factors. Efforts to prevent and address traffic violations in the jurisdiction of the Labuhan Batu Resort Police include pre-emptive, preventive, and repressive measures. The effectiveness of law enforcement against traffic violators in the jurisdiction of the Labuhan Batu Resort Police has not been effective because the police face many internal and external obstacles. Law enforcement is the process of making efforts to establish or ensure the functioning of legal norms as a guideline for behavior in traffic or legal relationships in social and state life.